2012
DOI: 10.1016/j.micres.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Sesbania grandiflora flower polyphenol extracts on some pathogenic bacteria and growth stimulatory effect on the probiotic organism Lactobacillus acidophilus

Abstract: Polyphenolic extracts (PE) of edible flower of Sesbania grandiflora were tested to evaluate its antimicrobial effect against some common pathogenic bacteria and growth promoting property against probiotic organism Lactobacillus acidophilus. The antimicrobial activity of S. grandiflora flower PE against selected pathogens was evaluated using both in vitro and in situ methods. In vitro studies suggested that PE has inhibitory effect against Staphylococcus aureus, Shigella flexneri 2a, Salmonella Typhi, Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 35 publications
1
49
0
4
Order By: Relevance
“…Generally, the presence of plant extracts does not affect the growth of microorganisms [20,21], but in some cases, they can benefit from the presence of these bio-components, increasing, for example, their survival during gastro-intestinal transit. This effect is influenced by both the type of strain and by the vegetable matrix [22].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the presence of plant extracts does not affect the growth of microorganisms [20,21], but in some cases, they can benefit from the presence of these bio-components, increasing, for example, their survival during gastro-intestinal transit. This effect is influenced by both the type of strain and by the vegetable matrix [22].…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that the roots of S. grandiflora possess antituberculosis activity [7]. The flower extracts of this plant have also been proved to possess antimicrobial activities [8]. In one of our previous studies we have found that the leaves of this plant possess protective roles against rat kidney during alcohol and polyunsaturated fatty acid induced oxidative stress [3].…”
Section: Introductionmentioning
confidence: 99%
“…[26] A number of plant extracts rich in flavonoids are known possess antimicrobial, anthelmintic, and cytotoxic potential. [27][28][29][30][31][32][33][34][35][36] The diverse therapeutic potential of plant flavonoids is due to their chemical structures. Such phytochemicals from plants serve as important therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%